Legal Policy Strategy for Banking Lending in Support of Sustainable Energy Sector to Achieve Community Welfare - Samosir, Redy Rahmad; Sulaiman, Abdullah; Barthos, Megawati (Interdiciplinary Journal and Hummanity (INJURITY), 2024)
The development of the sustainable energy sector in Indonesia is an important effort in supporting the transition to a green economy. This research delineates specific issues to be addressed, focusing on three main questions: (1) What policies govern the distribution of bank credit to support sustainable energy projects undertaken by micro, small, and medium enterprises (MSMEs) in Indonesia? (2) What is the role of government policies and related regulations in supporting sustainable energy financing? (3) What are the challenges that MSMEs face in securing financing for sustainable projects? (4) What areas are the critical areas for policy improvement and regulatory support? This research could explore innovative strategies to enhance understanding of green finance options and improve the readiness of MSMEs to engage with banks. This study contributes to the understanding of the intersection between banking policy, government regulation, and sustainable energy development in Indonesia.